Real-time monitoring and warning system in urban rivers - Sabam Parjuangan; Rionaldi Ali; Ari Purnama (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Urban rivers water quality is not suitable for use. The volume of river water in the city is fast full when it rains. Both of these problems need to be monitored. The purpose of monitored to give a warning to a community around the rivers. The rivers water quality determined base on the pH sensor, and turbidity sensor detection. The river water level is determined based on the results of ultrasonic sensor readings. The reading of three sensors is sent via GSM (General Service Mobile) communication network in SMS (Short Message Service) form. The reading also sent via internet data communication network to the server and displayed on web page form. This study indicates that all three sensors are able to detect pH, turbidity, and surface level of the river. The Sensors reading delivered via the GSM communication network, it provides real-time river water information. Whereas sensor readings sent via data communication networks provide river water information that is not real-time. Thus, sensor readings of water urban rivers better delivered via GSM on SMS form than via data communication on Web page form.